Pengaruh Ukuran KAP, Peran Komite Audit dan Financial Distress terhadap Audit Delay - Sapitri, Widia; Syofyan, Efrizal (Universitas Negeri Padang, 2024)
The aim of this research is to analyze the influence of the size of public accounting firms, the size of the audit committee, and financial distress on audit delay. The purposive sampling method was applied to get a sample of 110 companies. The data is obtained from the annual reports of property and real estate companies listed on the Indonesian Stock Exchange for year 2018-2022. The results show that the size of public accounting firms and the size of the audit committee have no effect on audit delay, while financial distress has a postiive effect on audit delay.